The Effect of Long-Term Addiction to Online Games on Hemoglobin Levels and Urine Sediment Crystals in Adolescents in Mataram City - Farhataini, Annisa; Pauzi, Iswari; Urip, Urip; Diarti, Maruni Wiwin (Balai Publikasi Indonesia, 2024)
Online gaming addiction has a negative impact on health, such as reduced sleep hours and changes in sleep patterns can lead to a decrease in hemoglobin levels in the blood. This decrease in hemoglobin has an impact, namely anemia. Besides that, it can also cause kidney disease, especially the formation of urine sediment crystals caused by sitting too much, not drinking enough water and moving little. Objective: To determine the effect of long-term addiction to online games on hemoglobin and urine sediment crystal levels in adolescents in Mataram City. Method: This study is an analytical observational research with a cross sectional approach of 24 samples. Using data in the form of blood hemoglobin and urine levels. Sampling techniques with purposive sampling methods and descriptive data analysis. Results: The results of the study of 7 respondents who were not addicted to online games had normal hemoglobin levels (29.16%), 9 respondents who were addicted to online games with mild anemia (37.5%) and 8 respondents with moderate anemia (33.3%). Negative (-) crystals were found in the urine sediments of 24 respondents. Conclusion: There is an effect on the hemoglobin levels of adolescents who are addicted to online games and negative crystals on urine sediments